The Opposition To Religion in The Coptic Church al'ab Matta Al-Miskeen as an example (1919 – 2006) (Journal of the College of Basic Education, 2025)
al'ab Matta represented a religious thought that was close to secularism because he believed that the church had deviated from true Christianity when it intertwined religion with the state. He viewed spiritual education as the church's primary role, and any role beyond that was a departure from its traditions. He believed that monasticism was the means to reform the church and that the church should not be a cause for the isolation of citizens, whether practically or spiritually. The church should neither oppose nor support one political regime over another. These views led to his marginalization from church positions, which he preferred to being a cause of conflict within the church. On the other hand, Patriarch Shenouda believed that reform begins with the social and cultural revival of the Copts, that the relationship between the church and the state is shaped by pressures and demands, and that the church acts as an intermediary between the state and the Coptic citizen. al'ab Matta saw the Patriarch's view as illegitimate, arguing that it had turned the church into a social club, an economic corporation, and a political party. He believed that keeping the church spiritual in society protects it from decay, and that it should not present itself as the political voice of the Copts.